2020
DOI: 10.1055/s-0040-1710299
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Patterns and Prevalence of Streptococcus Agalactiae Rectovaginal Colonization Among Pregnant Women in Iran

Abstract: Objective Streptococcus agalactiae is an important pathogen in neonates and pregnant women. Neonatal invasive infections due to S. agalactiae are life-threatening and preventive strategies for this challenge of human have become a concern. The aim of the present study was to determine the prevalence of rectovaginal colonization, related risk factors and antibiotic resistance pattern of S. agalactiae among pregnant women in Iran. Methods The present study was performed on 240 pregnant women. Vaginal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
2
7
1
Order By: Relevance
“…Previously, both symptomatic and asymptomatic bacteriuria studies have also been conducted in Bangladesh, 37 Ethiopia, 38 and Iran. 36 Symptomatic bacteriuria, similar to the current study, was also reported in Pennsylvania, 39 Iran, 40 and India. 41…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Previously, both symptomatic and asymptomatic bacteriuria studies have also been conducted in Bangladesh, 37 Ethiopia, 38 and Iran. 36 Symptomatic bacteriuria, similar to the current study, was also reported in Pennsylvania, 39 Iran, 40 and India. 41…”
Section: Discussionsupporting
confidence: 89%
“…coli , Klebsiella , Pseudomonas, and other uropathogenic bacteria have also been reported. 5 , 35 , 36 , 41 , 43 , 50 , 51 , 52 The current study revealed that for uncomplicated and complicated bacteriuria, carbapenems should be preferred over fluoroquinolones and cephalosporins. The data from the current study highlights the need for antibiotic stewardship and the development of new effective antimicrobials that are safe for use in pregnancy.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Chemoprophylaxis still the most effective ways for prevention of GBS infections in mothers and neonates [24]. in the current work the GBS strains isolated from pregnant women was 100% susceptible to linezolid and vancomycin followed by ampicillin (93.1%) and tobramicin (83.9%) then gentamicin (81.6%) and levofloxacin(78.2%) and showed least antibiotic susceptibility to erythromycin (26.4%).…”
Section: Discussionmentioning
confidence: 58%
“…Out of 540 pregnant women 87 (16.1%) were colonized with GBS isolates, their age were 26 (24-33) years old. The positive GBS women aged 25 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) and negative GBS women aged 23 (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) with no statistical difference. Patients aged more than 35 years old has the higher rate of positive GBS, 46.2%.…”
Section: Resultsmentioning
confidence: 95%